Makna Rasa Syukur: Pembentukan Karakter Anti-Korupsi Berlandaskan Agama Islam - Daulay, Dwi Revalina; Febrianty, Adelia (Proceedings of International Conference on Muslim Society and Thought, 2024)
The purpose of this study discusses the meaning of gratitude: the formation of anti-corruption character based on Islam. This research method uses qualitative methods by collecting data through literature studies sourced from primary data in the form of scientific papers from various journals and secondary data sourced from books and modern articles. Corruption is a familiar topic for all people because this problem has never been resolved. In general, the average corruption problem comes from dissatisfaction in obtaining and doing something. Gratitude is something that can be a character that can be built in eradicating corruption because in controlling gratitude someone will know which is meant by need and which is meant satisfaction. By being grateful, one will be able to receive all the blessings obtained so as to prevent negative behavior such as corruption. But it is not only the nature of gratitude that must be instilled in building anti-corruption traits, there are other characteristics that need to be instilled as well. This research has limitations in conducting field study research through interviews, so this is an opportunity for further research for empirical studies in a more measurable manner. This research is recommended to put more emphasis on field studies that link gratitude with acts of corruption.